Organization of the Lithuanian Government in Exile in the Years 1941–1943 in United States: Establishment of Lithuanian National Council (Parliamentary Studies, 2020)
This article discusses the attempt to create a Lithuanian Government in exile among the Lithuanian immigrants who reached the United States in 1939–1941. This topic has not been given enough attention in historical literature yet, therefore the article is based on archival documents and articles from Lithuanian American press of the time. The article explores the founding of the Lithuanian Citizens Union and its struggles as well as the opinions of the former President of Lithuania A. Smetona, other Lithuanian American organisations (the Lithuanian American Council in particular) and Lithuanian representatives in the US towards this event. Moreover, the paper reveals the backstage of establishing the Lithuanian National Council, its first steps and, later on, its decadence.
Keywords: Lithuanian citizens; Lithuanian Americans; Lithuanian American Council; Lithuanian Government in exile; Lithuanian National Council; Povilas Žadeikis; Leonardas Šimutis; Petras Vileišis; Kazys Grinius; Kazys Pakštas; Petras Daužvardis; newspaper ‘Draugas’